Marginal integrity of two zirconia-based crowns before and after porcelain veneering - Sakineh Nikzad; Abbas Azari; Mani Arashrad; Ghazal Arashrad (Tehran University of Medical Sciences, 2013)
Background and Aims: The marginal integrity of fixed restorations always is a major matter of concern for dental clinicians. Any cause of distortion, including veneering processes, in the marginal integrity is supposed to be detrimental for long-term success of fixed dental prostheses. The aim of this in vitro study was to compare the marginal adaptation of two different full ceramic restoration systems (Zirkouzahu&Cercon) and possible changes in marginal integrity following the multiple veneering process. Materials and Methods: Twelve all-ceramic crowns in the form of coping were fabricated on a pre-made standard metal die with finish line of shoulder preparation from two commercial systems: Cercon® and Zirkonzahn®. The specimens were not cemented. The Crown/Die discrepancy were measured by means of a precise stereo microscope (accuracy±0.1 μm), at various points (n=12) selected along circumferential margin of the restorations. Same procedure was accomplished after applying the veneering porcelain. The mean gap dimensions were calculated and data were analyzed by multivariate (b) test. Results: Mean marginal gap dimensions before and after veneering porcelain firing cycles, for Cercon® were (59.67±13.46 µm) and (63.75±14.16 µm) and for Zirkonzahn® were (65.81±24.37 µm) and (64.74±21.94 µm), respectively. Hotelling trace Multivariate(b) test method showed that the rate of mismatching marginal integrity in two groups (Cercon® and Zirkonzahn®) had no significant difference before and after porcelain firing (P>0.05). Conclusion: Within the limitation of this study, the marginal integrity of both systems were seems to be within the clinically acceptable standard dimension, i.e. 120μm.The marginal gap of both all-ceramic systems were not affected by veneering porcelain firing cycles.